Impunity in computer crimes. A problem of little interest to legislators, judges and prosecutors - Estrada Salvador Ramirez, Catalina Tania (2024)
This article originates from the problem that has been observed in the prosecution and punishment of computer crimes, since many of these criminal cases usually go unpunished. In this line of ideas, through the aforementioned study, the factors that contribute to the non-criminal punishment of cybercriminals will be fully identified. One of these factors is the non-individualization of the cybercriminal, which is why the representative of the Public Ministry usually files the criminal process, for a simple reason: the formalization of the preparatory investigation requires the full individualization of the subject, otherwise, the investigation cannot be formalized. In order to avoid impunity for computer crimes, this research will provide certain solutions that will contribute to the investigation and punishment of these criminal acts.